2019
DOI: 10.2174/0929867325666180430152023
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry of Potassium Channel Modulators: An Update of Recent Progress (2011-2017)

Abstract: This review discussed the current understanding of medicinal chemistry research in the field of potassium channel modulators to update the key advances in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…ampening cellular electrical activity by pharmacological activation of specific types of K + channels has therapeutic potential for the treatment of a variety of disease states, including epilepsy, arrhythmias, vascular constriction, and various pain conditions (1,2). Consequently, screening efforts have identified a number of agents that open different types of K + channels (2), presumably by targeting their respective channel-specific activation mechanisms.…”
mentioning
confidence: 99%
“…ampening cellular electrical activity by pharmacological activation of specific types of K + channels has therapeutic potential for the treatment of a variety of disease states, including epilepsy, arrhythmias, vascular constriction, and various pain conditions (1,2). Consequently, screening efforts have identified a number of agents that open different types of K + channels (2), presumably by targeting their respective channel-specific activation mechanisms.…”
mentioning
confidence: 99%
“…When extracellular K + concentration increasing, it subsequently causes neuronal membrane depolarization (Tang et al., 2010). As the membrane is depolarized in neuronal firing activity, the central ion pore of Kv channels will open for K + efflux, thus drives the membrane potential toward a negative direction, which leads to repolarization in action potential, and finally quiets the cell activity (Vyas et al., 2019; Wu et al., 2015).…”
Section: Genetic Dysfunction Of Potassium Channels and Asd: From Genotypes To Phenotypesmentioning
confidence: 99%
“…It was reported that about 15 Kir clones were identified and classified in seven different families (Kir1 through Kir7) based on their sequence similarities and functional properties (Binda et al., 2018). Kir channel contains two transmembrane regions and a pore‐forming domain, permitting K + to move into the cell and are often regulated by intracellular factors, like ATP‐sensitive potassium channels (Vyas et al., 2019) (see Figure 3). Aberrant Kir channel expression and function may lead to defective brain development and an imbalance of K + homeostasis in the brain, which could finally result in neuropsychiatric and developmental disorders (Sun et al., 2018).…”
Section: Genetic Dysfunction Of Potassium Channels and Asd: From Genotypes To Phenotypesmentioning
confidence: 99%
“…Bai found that over-expression of miR (short non-coding RNA molecules)À296-3p sensitised glioblastoma cells to anticancer drugs, whereas downexpression using antisense oligonucleotides conferred MDR (Bai et al, 2013). Meanwhile, it has been found that a large number of toxins and drugs have the ability to regulate K þ channels, which can be used to block K þ channels or change channels' sensitivities to voltage and calcium concentration (Vyas et al, 2019).…”
Section: Blockers Of K þ Channel and Treatments Of Gliomasmentioning
confidence: 99%